Compliance Assessment in the Renewal of the Building Worthiness Certificate - Syapril Janizar; An An Anisarida (Politeknik Siber Cerdika Internasional, 2026)
Background: The Building Worthiness Certificate (Sertifikat Laik Fungsi/SLF) is a mandatory instrument under Indonesian building law that ensures buildings meet functional and safety standards. For non-residential buildings, SLF validity is limited to five years, necessitating periodic renewal assessments. Despite its importance, empirical studies on the SLF renewal process remain scarce, particularly for industrial facilities. Objective: This study aims to evaluate the compliance level of the PT X Industri building in Bandung against applicable technical and regulatory standards during the SLF renewal process, and to identify technical and administrative gaps that may hinder successful certification renewal. Methods: A descriptive qualitative approach with a single-case study design was employed. Primary data were collected through systematic building inspections covering structural systems, fire protection systems, accessibility, and evacuation systems, supported by semi-structured interviews with building managers and SLF consultants. Secondary data included technical drawings, regulatory documents, and maintenance records. Results: The structural system demonstrated adequate capacity, with a maximum P–M–M (axial force–bending moment–bending moment) interaction ratio of 0.802 (< 1.0), in compliance with SNI 1726:2019. However, deficiencies were identified in fire protection, barrier-free accessibility, evacuation signage, and the completeness of technical documentation, all of which were non-compliant with the respective regulatory standards. Conclusion: The SLF renewal process serves not merely as an administrative formality but as a comprehensive building performance evaluation mechanism. Systematic maintenance programs, enhanced safety facilities, and the digitalization of technical records are recommended to support continuous building quality assurance.